Legal pacifism - García Sáez, José Antonio (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
War and peace could be thought as two moments bound to succeed each other within the history of international relations. But there is also room for the hope in a perpetual or, at least, sustainable peace thorough the development of a strong international order. Several legal scholars, whose works can be labelled inside the legal pacifism, have devoted their efforts to that end. This paper tries to put some order about the main features of legal pacifism. It takes as a central division their position towards war: some legal pacifists have defended the total outlawry of war, while others have considered preferable a progressive overcoming of war. Both positions will share the preference for strength the international institutions, together with a certain degree of cosmopolitan commitment.